Manajemen Kerjasama Sekolah dengan Dunia Usaha Dunia Industri (Du/Di) dalam Meningkatkan Skill Kerja Di SMKN 10 Agribisnis dan Agrotek Merauke - Priyudahari, Bhujangga Ayu Putu; Nurhayati, Nurhayati (FKIP Universitas Wisnuwardhana, 2024)
aduates. Given that SMK is a school that prepares its graduates for the workforce, it is worth considering whether there is room for improvement in this area. It seems that there is a discrepancy between the curriculum provided by schools and the needs of the business and industrial world (Du/DI). This suggests that there is a need for a collaborative partnership between Du/DI and schools to ensure that the curriculum aligns with the requirements of the workplace. It would be beneficial for partners to provide input on the needs of the world of work, which could then be taken into consideration by schools for the curriculum. Partners could also play an active role in providing direct learning in the form of work training (internships) or other activities. This research aims to gain insight into the management of the partnership between SMK 10 Agribusiness and Agrotek Merauke with Du/DI, and to understand the role that this partnership plays. This study employs qualitative research methods to gain a deeper understanding of the management of the partnership between SMK 10 Merauke and its partners. This research aims to shed light on the valuable role partners can play in aligning SMK curriculum with the needs of the world of work. Beyond this, partners can also contribute to students' professional development through internships or by sharing their expertise as guest lecturers. This research hopes to highlight the significance of collaborative management in enhancing students' skills and employability by offering insights into the curriculum and providing academic guidance